Design, synthesis, and anticancer activity of novel 4-thiazolidinone-phenylaminopyrimidine hybrids - TÜRE, ASLI; KÜÇÜKGÜZEL, İLKAY (SPRINGER, 2021)
4-Thiazolidinones and phenylaminopyrimidines are known as anticancer agents. Imatinib is the pioneer phenylaminopyrimidine derivative kinase inhibitor, which is used for the treatment of chronic myeloid leukemia. With a hybrid approach, a novel series of 5-benzylidene-2-arylimino-4-thiazolidinone derivatives containing phenylaminopyrimidine core were designed, synthesized, and tested for their anticancer activity on K562 (chronic myeloid leukemia), PC3 (prostat cancer), and SHSY-5Y (neuroblastoma) cells. Since superior anticancer activity was observed on K562 cells, further biological studies of selected compounds (8, 15, and 34) were performed on K562 cells. For the synthesis of designed compounds, thiourea compounds were converted to 2-imino-1,3-thiazolidin-4-ones with alpha-chloroacetic acid in the presence of sodium acetate. 5-Benzylidene-2-imino-1,3-thiazolidin-4-one derivatives were obtained by Knoevenagel condensation of 2-imino-1,3-thiazolidin-4-ones with related aldehydes. Compounds 8, 15, and 34 were evaluated for cell viability, apoptosis studies, cell cycle experiments, and DNA damage assays. IC50 values of compounds 8, 15, and 34 were found as 5.26 +/- 1.03, 3.52 +/- 0.91, and 8.16 +/- 1.27 mu M, respectively, in K562 cells. Preferably, these compounds showed less toxicity towards L929 cells compared to imatinib. Furthermore, compounds 8 and 15 significantly induced early and late apoptosis in a time-dependent manner. Compounds 15 and 34 induced cell cycle arrest at G0/G1 phase and compound 8 caused cell cycle arrest at G2/M phase. Based on DNA damage assay, compounds 8 and 15 were found to be more genotoxic than imatinib towards K562 cells. To put more molecular insight, possible Abl inhibition mechanisms of most active compounds were predicted by molecular docking studies. In conclusion, a novel series of 5-benzylidene-2-arylimino-4-thiazolidinone derivatives and their promising anticancer activities were reported herein. [GRAPHICS] .
Keywords: Phenylaminopyrimidines; 2-Arylimino-4-thiazolidinone derivatives; Anticancer agents; Apoptosis; Molecular docking; IN-VITRO EVALUATION; BIOLOGICAL EVALUATION; KINASE INHIBITORS; TYROSINE KINASE; NONNUCLEOSIDE INHIBITORS; ANTIMICROBIAL ACTIVITY; 4-THIAZOLIDINONES; DERIVATIVES; ANTITUBERCULOSIS; MECHANISM